Sprawiedliwość w sędziowskim wymiarze kary - Królikowska, Jadwiga; Utrat-Milecki, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article starts with the general presentation of the sociological perspective on the question of justice in the motives of a criminal judge’s sentencing decisions. The question of justice is also analysed in relation to the legitimation of the criminal law and the various theories of punishment, retributive, consequentialist, and mixed. Punishment is analysed as a social and legal institution and as a social process in its various organisational forms. The rationalisation of punishment as a social and legal institution is analysed in relation to the question of human rights, and the question of its effectiveness in social control as a tool in the protective function of the criminal law. The problem of justice is also analysed from a subjective point of view as a question of the just judge. It is not only analysed here as an ethical question, but also as a problem of the methodology of the work of the judge, and a question of organisation of the sentencing process. The article presents the results of research sociological reports concerning the question of the motives of judges’ sentencing in the criminal courts. The article presents the basics of the methodology and results of research in that respect which was carried out in the 1930s B.Wróblewski, W. Świda, 60s and 70s T. Kaczmarek, W. Świda, and the 1980s T. Kaczmarek, J. Giezek and the team, and the latest research carried out by the authors in 2012–2015 J. Królikowska, J. Utrat-Milecki. The authors explain here the general outline of the method of culturally integrated social and legal studies, which they used in their sociological and anthropological research on the criminal justice offi cers judges, prosecutors and probation officers, and which is also the theoretical background of the present article. Finally, the authors present the broader culturally integrated definition of punishment, so as to help to identify the main research questions in socio-legal studies of punishment considered both as a socio-legal institution and a social and legal process which can be identified in different organisational forms.
Keywords: sprawiedliwość; kara; wymiar sprawiedliwości; sędzia; penologia; instytucja społeczno-prawna; wyroki; kulturowo zintegrowane nauki społeczne i prawne; prawa człowieka; kontrola społeczna